Association of physical–mental comorbidity with cognitive decline in middle-aged and older adults in China, India and Indonesia: a multiple country large scale data cross-sectional comparative study - Siqi Zhao; Xing Ye; Yang Zhao; Kanya Anindya; Tiara Marthias; Mercian Daniel; Tianhao Zhao; Li Han (Chinese General Practice Journal, 2025)
Background: Growing evidence suggests a strong association between multimorbidity and brain health in older adults. However, limited studies have examined the combined impact of physical and mental multimorbidity on cognitive decline. Objective: This study aims to investigate the relationship between physical-mental multimorbidity and cognitive decline. Methods: This study utilized three nationally representative survey data from China (China Health and Retirement Longitudinal Study), India (Longitudinal Aging Study in India), and Indonesia (Indonesian Family Life Survey), including a total sample of 73,119 respondentse. Cognitive function was assessed across three domains: time orientation, word recall, and numeracy. Multivariable linear regression model was used to examine the association between physical-mental multimorbidity and cognitive decline, adjusting for sociodemographic and lifestyle factors. Results: Physical-mental multimorbidity was significantly associated with lower cognitive function scores in China (β= -6.99; 95 % CI: -8.26, -5.71), India (β= -2.76; 95 % CI: -3.41, -2.11), and Indonesia (β= -2.75; 95 % CI: -4.10, -1.41). Stratified analyses revealed stronger associations among women and individuals with higher socioeconomic status compared to men and those with lower socioeconomic status. Conclusion: Cognitive decline is highly prevalent among individuals with depressive symptoms and physical-mental multimorbidity. Addressing mental health issues in individuals with multimorbidity may help reduce the risk of cognitive impairment and dementia in aging populations.